Analisis Penguatan Budi Pekerti Pada Kurikulum Merdeka Melalui Pembelajaran Bahasa Jawa Di SD Negeri Sawojajar 1 - Silviani Nur Ajizah; Rila Melyana Fitri; Moh. Toharudin (Concept: Journal of Social Humanities and Education, 2023)
The main problem in this reseach is how strengthen character in the independent curriculum in forming character in grade 1 students, the process of applying ethical values to students and the results of strengthening character though learning Javanese. This type of research is descripve qualitative. In this study the data collection used included: observation, in-depth interviews, and documentation.the analytical method used is three stages, namely data reduction, data presentation, and verification. In learning Javanese, habituation can be carried out if the school environment can play a role in the habituation of learning Javanese, including the use of spoken language, behavior, and habits of these factors that have an influence on students, based on the research results that has been done, it can be concluded that the analysis of strengthening character in the independent curriculum through learning Javanese at SD Negeri Sawojajar 1 is carried out with good.